2015
DOI: 10.1093/brain/awv306
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted sensorimotor and social–cognitive networks underlie symptoms in childhood-onset schizophrenia

Abstract: Schizophrenia is increasingly recognized as a neurodevelopmental disorder with altered connectivity among brain networks. In the current study we examined large-scale network interactions in childhood-onset schizophrenia, a severe form of the disease with salient genetic and neurobiological abnormalities. Using a data-driven analysis of resting-state functional magnetic resonance imaging fluctuations, we characterized data from 19 patients with schizophrenia and 26 typically developing controls, group matched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
76
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(86 citation statements)
references
References 114 publications
10
76
0
Order By: Relevance
“…We also found reduced functional connectivity of the sensorimotor network in schizophrenia compared to healthy controls, similar to prior studies (e.g., Berman et al, 2016). Sensorimotor regions are implicated in low-level shared representations of action perception, or mirroring (e.g., Caspers, Zilles, Laird, & Eickhoff, 2010;Iacoboni, 2009).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We also found reduced functional connectivity of the sensorimotor network in schizophrenia compared to healthy controls, similar to prior studies (e.g., Berman et al, 2016). Sensorimotor regions are implicated in low-level shared representations of action perception, or mirroring (e.g., Caspers, Zilles, Laird, & Eickhoff, 2010;Iacoboni, 2009).…”
Section: Discussionsupporting
confidence: 89%
“…Studies of the DMN in schizophrenia have shown both hypoconnectivity and hyperconnectivity within the network compared to controls (Fornito, Zalesky, Pantelis, & Bullmore, 2012;Narr & Leaver, 2015;Sheffield & Barch, 2016). DMN connectivity with sensorimotor and affective networks is also reduced (Berman et al, 2016;Martino et al, 2018).…”
mentioning
confidence: 99%
“…In addition to the DMN and SN, intra‐SMN connectivity also plays an important role in discriminating schizophrenia from HCs. As reported in a recent study, intra‐SMN connectivity is related to the severity of the positive symptoms of schizophrenia [Berman et al, ].…”
Section: Discussionmentioning
confidence: 87%
“…A recent paper by Berman et al (2016) describes the phenomenon of childhoodonset schizophrenia, a 'pure' form of the disorder observed without the often confusing correlates of an extended disease course (Lancaster and Hall 2016 Lancaster and Hall (2016) find that the results of Berman et al are compatible with a pathodevelopmental model in which patients with childhood-onset schizophrenia experience excessive 'over-pruning' of short-distance functional connections.…”
Section: Discussionmentioning
confidence: 99%